Efficacy of German chamomile mouthrinse on plaque, gingivitis, periodontal pockets and calculus in man - K. Younis, Shaymaa; D. Salman, Faraed (Tikrit Journal of Pharmaceutical Sciences, 2023)
The aims of this study werc to evaluate the effectiveness of German chamomile extract as a mouthrinse on the development of plague, gingivitis, pathological pockets and calculus in man to determine whether it can provide any benefit without the addition of other additives.Fifty adult volunteers participated in this controlied single blind cross-over study. The subjects used either German Chamomile or a chlorhexidine mouthrinse for 1 minute twice daily during eight weeks period. 2 weeks interval between each visit for motivation and reinforcement of application of the material Four applied indices (plaque and gingival indices by Loe and Silness), CPITN index by Ainamo and calculus index by Ramfjord were recorded at baseline, after each experimental period and at the last visit. The mean reduction in plaque. gingival and periodontal pocket depths were determined by using paired Z-test between each visit at P< 0.01 significantly lower for GC than for CHX mouthrinse. While for calculus index there was significant increase between each visit at P< 0.05 using paired Z-test and for all visits using repeated measures F-test at P <0.01.Using GC mouthrinse in a percentage of 1:4 appears to offer benefit in plaque, gingival, pocket depth reductions but with significant adverse increase in calculus index.